Surgical Tips in Frozen Abdomen Management: Application of Coliseum Technique - Ioannis D. Kyriazanos; Dimitrios K. Manatakis; Nikolaos Stamos; Christos Stoidis (Case Reports in Surgery)
Wound dehiscence is a serious postoperative complication, with an incidence of 0.5–3% after primary closure of a laparotomy incision, and represents an acute mechanical failure of wound healing. Relatively recently the concept of “intentional open abdomen” was described and both clinical entities share common pathophysiological and clinical pathways (“postoperative open abdominal wall”). Although early reconstruction is the target, a significant proportion of patients will develop adhesions between abdominal viscera and the anterolateral abdominal wall, a condition widely recognized as “frozen abdomen,” where delayed wound closure appears as the only realistic alternative. We report our experience with a patient who presented with frozen abdomen after wound dehiscence due to surgical site infection and application of the “Coliseum technique” for its definitive surgical management. This novel technique represents an innovative alternative to abdominal exploration, for cases of “malignant” frozen abdomen due to peritoneal carcinomatosis. Lifting the edges of the surgical wound upwards and suspending them under traction by threads from a retractor positioned above the abdomen facilitates approach to the peritoneal cavity, optimizes exposure of intra-abdominal organs, and prevents operative injury to the innervation and blood supply of abdominal wall musculature, a crucial step for subsequent hernia repair.